Etude et conservation-restauration d’un Qilin en émail cloisonné chinois provenant du musée des Arts décoratifs de Paris - Aude Lafitte (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The documentary background on Chinese cloisonné enamels is incomplete, therefore its conservation enables the better understanding of their origin, technical nature and history. The last year of conservation studies at the Institut national du patrimoine was focused on the study of an 18th-century Chinese cloisonné enamel from the Arts décoratifs Museum (Paris). A research was carried out on the use of paper rubbers for the cleaning of copper cloisons gilded with mercury amalgam. Cleaning operations were completed by the use of peelable gel on large gilded areas, the dismantling and cleaning, as well as the conservation of the enamel.